Genetic variation at ASIP and KAP1.1 gene loci in indigenous sheep - Yadav, Harikesh Singh; Gupta, Ranjan; Arora, Reena (Journal of Livestock Biodiversity, 2025)
The study reports the polymorphism in the ovine Agouti Signalling Peptide (ASIP) and the keratin associated protein (KAP1.1) gene loci in four indigenous sheep breeds namely Marwari, Jaisalmeri, Malpura and Kheri. At the ASIP gene locus two alleles were observed in all sheep breeds. The frequency of the predominant allele ranged from 0.819 to 0.986 with an overall average of 0.934 across the four sheep breeds. The KAP1.1 gene locus across the four sheep breeds revealed the presence of 4 alleles. All tested animals were observed to be heterozygous. These preliminary results contribute to the assessment of genetic diversity available within genes associated with wool quality traits in indigenous sheep genetic resources.